(untitled) (Andamios, Revista de Investigación Social, 2012)
The goal of this article is to show an historiographic balance based on the study of the publications about the Student Movement of 68 during the decade of 1998-2008. The main reason that guides almost all the analyzed texts is the October 2nd repression. However, at the bibliographical production some thematic elements linked with the movement analysis appear. Inside the interpretations about the topic it was possible to identify some consensus points, particularly emphasizing the causes of the Movement, the involved collective actors, and also the effectiveness of the forms of struggle. The most evident divergences are related with the projects and the impact of the mobilization in the political and social system.